Scoping review of methods of monitoring acute changes in lower body neuromuscular function via force plates - Andrew J. Badby; Nicholas J. Ripley; John J. McMahon; Peter D. Mundy; Paul Comfort (PLoS ONE, 2025)
Force plates are amongst the most utilised technological apparatus for monitoring acute changes in neuromuscular function in sports. Practitioners apply monitoring strategies to manage neuromuscular fatigue and physical preparedness with valid, reliable, and sensitive measures. The aim of this scoping review was to identify, map, and describe the variety of monitoring procedures which have been previously applied in research (e.g., test and metric selection, data collection, study design, and data analysis procedures). Searches were completed by 24th June 2024. One thousand, nine hundred, and seventy-eight studies were identified across four databases (PubMed, EBSCO, Clarivate web of science, and Ovid). After removing duplicates, applying the inclusion criteria, and scouring the reference lists of remaining studies, a final total of thirty studies of within-group repeated measures design were used in this review. Major differences were identified across all aspects of studies methodologies, such as in subject demographics (e.g., sex, sport, and competitive level), data collection protocols (e.g., force plate hardware utilised, test and metric selection, verbal cues, and provision of information regarding testing surface, familiarisation and warm-up provided, the process of zeroing force plates between trials, and weighing of subjects during trials), and study design (e.g., reference physical activity investigated, time of season, testing timepoints, and training load determination). A general lack of reporting and uniformity in metric definitions, metric calculations, and phase terminology was identified across studies. For example, two separate calculations were reported for “peak force” across studies, as either “the maximum force achieved throughout the entirety of the trial”, or as “the maximum force achieved during the propulsion phase”. The latter calculation was also utilised for “peak concentric force” in a separate study. Thus, an accurate comparison of results across studies (e.g., via meta-analysis) and forming any generalized conclusions about the application of specific tests and metrics for monitoring acute changes in neuromuscular function using force plates was premature at this time. The information presented in this review will contribute towards forming a rationale for the data collection, study design, and data analysis protocols for future research on monitoring acute changes in neuromuscular function using force plates.